1989
DOI: 10.1007/bf00277261
|View full text |Cite
|
Sign up to set email alerts
|

Binding specificity and intramolecular signal transmission of uncleaved insulin proreceptor in transformed lymphocytes from a patient with extreme insulin resistance

Abstract: An alteration of an amino acid sequence in the processing site of the insulin proreceptor by a point mutation of the insulin receptor gene produced extreme insulin resistance. We characterized functional properties of the unprocessed insulin receptor in transformed lymphocytes from a patient. Insulin binding to intact cells and to a partially purified insulin receptor preparation was radically decreased to 20% and 18% of the control values, respectively. In competitive insulin binding to intact cells, [LeuA3]-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The method for the 125I-insulin binding to erythrocytes, transformed lymphocytes, and cultured fibroblasts has been described by Sasaoka et al 5 6 Surface labelling of Epstein-Barr virus transformed lymphocytes was determined by the method described previously. 7 We performed subsequent DNA analysis of insulin receptor gene by a modification of the method described by Kusukawa et al8 and examined transfection of insulin receptor c-DNA to COS7 cells according to the method of Kobayashi et al 9 Recombinant human IGF-I was provided by the Fujisawa pharmaceutical industry (Osaka, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…The method for the 125I-insulin binding to erythrocytes, transformed lymphocytes, and cultured fibroblasts has been described by Sasaoka et al 5 6 Surface labelling of Epstein-Barr virus transformed lymphocytes was determined by the method described previously. 7 We performed subsequent DNA analysis of insulin receptor gene by a modification of the method described by Kusukawa et al8 and examined transfection of insulin receptor c-DNA to COS7 cells according to the method of Kobayashi et al 9 Recombinant human IGF-I was provided by the Fujisawa pharmaceutical industry (Osaka, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Insulin binding to transformed lymphocytes. The method of 125I-insulin binding to transformed lymphocytes has been described elsewhere [5]. The binding study was carried out at 15 ~ for 3.5 h.…”
Section: Me~o~mentioning
confidence: 99%
“…Preparation of partially purified insulin receptor. The method of purifying insulin receptors, using WGA agarose column has been described previously [5].…”
Section: Me~o~mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, it was recently shown that the expression of a deletion mutant of IGF-IR lacking the 36 amino acid residues immediately NH 2 -terminal to the transmembrane domain of IGF-IR (IGF-IR ⌬870 -905 ) in BALB/c 3T3 cells resulted in the intracellular accumulation of a high-molecular-mass (ϳ200 kDa) proreceptor (13). Another study showed that the insulin proreceptor can bind insulin (14); it is therefore possible that the structurally similar IGF-IR proreceptors can also retain a ligandbinding capacity.…”
Section: Inhibition Of Liver Metastasis By Igf-ir Extracellular Domainmentioning
confidence: 99%